Preparation and Luminescence Properties of Europium(III) and Tungstate Co-doped in Silicate Materials via The Sol-Gel Method - XIA, LI; XIGUI, WANG; YIN, ZHANG (Asian Journal of Chemistry, 2010)
In the preparation of this precursor tetraethylortho silicate (TEOS), sodium tungstate, ethyl alcohol and HCl were mixed and then heated at different temperatures for 3 h, leading to a luminescent compound. TGDTA and IR show the stable and network structure of luminescence material. The three-dimension fluorescence spectra, excitation and emission spectra were used to characterize the luminescence properties of Eu3+ doped silica materials. The results indicate that the luminescence materials were excited by 7F0→5L6 transition of Eu3+ at 393 nn and the bands in the emission spectrum are corresponding to the 5D0→7FJ (J = 0, 1, 2) transitions of europium ion. The strongest band is the electronic dipole transition and the material in green lights. Furthermore, we found that WO42- absorbed most of the energy and transferred to rare earth ion Eu3+ effectively. The effect of WO42- on the glass network and neighbouring configuration of Eu3+ is discussed based on the optical spectra. The f-f transitions of the materials were interpreted by energy level of the luminescence materials. In this paper, we have also investigated the influence of tungstate content and annealing temperature in europium doped silicate materials on luminescence properties. Finally, the doped agent WO42- sensitized the luminescence intensity of rare earth Eu3+ more than 6 times when doped quantity is up to 3.26 %.